What Do Arts-Based Methods Do? A Story of (What Is) Art and Online Research With Children During a Pandemic. (September 2022) - Spray, Julie; Fechtel, Hannah; Hunleth, Jean
This comic draws viewers behind the final product and into the process of arts-based research. Specifically, we focus on research produced over Zoom during the Covid-19 pandemic. Based on a study of asthma caregiving, we illustrate how a 10-year-old study participant, Becca, and researcher Hannah connected in embodied, sensory and material-spatial ways across digital space through the making and unmaking of art forms using simple sensory-sculptural materials (pipe cleaners, play-doh, balloons). We consider what arts-based methods do : for the participant, the researcher, their relationship, and ethical knowledge production. And we show what research processes can look like as unpredictable, messy and patient communing.